Strategic competence in solving financial problems: a case study of climbers students - I Sabilah; T Y E Siswono; M Masriyah (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Strategic competencewas mental activities apply strategies to formulate, represent, and solve mathematical problems. The aim ofqualitative research is to explore strategic competence of climber student in solving financial problems.In this case, we selected from 40 students who has different adversity quotient to 3 climber students. Data based on semi-structured interview was analyzed by some steps that was consist of data condensation, data display and drawing/verification conclusion. The result pointed out that student understood the problem by reading and recall prior knowledge. They formulate problem solving by understanding mathematical formulation. Student solving financial problems by numerical and verbal strategy. Finally, they determine effective solution using arithmetical method, then find cheaper solution. For the next research, we could give a suggestion to exploring another students’ adversity quotient.